O acesso às políticas públicas pelas comunidades quilombolas do Município de Ponta Grossa - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
The object of this dissertation is to configure the quilombola territories in the municipality of Ponta Grossa and its interface with the public policies of the municipal network, from the perspective of the quilombola communities Colônia Sutil and Santa Cruz. The objectives outlined for carrying out the research were, in general: to analyze the configuration of quilombola territories in the municipality of Ponta Grossa and its interface with municipal public policies; specific: characterize socially / economically quilombola communities, through socioeconomic profile; understand the social demands presented by quilombola communities for public policies; to verify how quilombolas and representatives of public services evaluate the interface between public policies; map the network of public services to which quilombolas do have access.To achieve the proposed objectives, the methodology of a qualitative nature, used the following methodological instruments: bibliographic research, form, interview, observation and record in a field diary. Through field research, 20 families were counted in Colônia Sutil, with 9 (nine) forms being applied, the president of the residents' association and the oldest resident of the community were also interviewed.In the Santa Cruz Community, 10 (ten) families were counted, 3 (three) forms were applied, and the local quilombo representative was interviwed. From the literature review on the categories surroundig the presente study , field research was carried out. Contextualing municipaly of Ponta Grossa, and analyzing the data through contente analysis, ir was possible to trace the socioeconomic profile of quilombola communities, analyze the categories of territory and community, and how access to public policies is configured by the quilombola communities surveyed. The dissertation consisted of two chaperts. Access to public policies by the quilombola communities in the municipality of Ponta Grossa proved to be weakened. The research subjects do not have access on a continuous basis, in view of where they are located, and the access to mean of transport.
Keywords: Comunidade quilombola; política pública; território; Quilombola Community; Public Policy; Territoty; CNPQ::CIENCIAS SOCIAIS APLICADAS